A series of color-tunable light-emitting open-framework lanthanide sulfates containing extra-large 36-membered ring channels. Issue 40 (29th September 2017) - Xue, Yun-Shan; Shi, Dayou; Zhang, Haitao; Ju, Weiwei; Mei, Hua; Xu, Yan
Abstract : A series of lanthanide sulfates contain 36-ring channels with the pore size (22.0 × 16.8 Å) based on Eu10 clusters. Abstract : A series of isostructural lanthanide sulfates LnSO4 -NTU1 (Ln = Eu (1 ), Tb (2 ), Sm (3 ), Dy (4 ), and Er (5 )) containing extra-large 36-membered ring (36-MR) channels were prepared by employing "scale chemistry" theory with cluster building units. The 2-fold interpenetrated dia network was assembled with tetrahedral Ln10 (SO4)16 clusters. A single dia framework contains 36-MR channels with the pore size (22.0 × 16.8 Å) reaching the mesoscale. The discovery of LnSO4 -NTU1 sets a new record, pushing the existing maximum channel size of metal sulfates from 24-MR forward up to 36-MR. Notably, mix-Eu/TbSO4 -NTU1 exhibits color-tunable luminescence from red to green through adjusting the molar ratio of Eu : Tb in the frameworks.